Implementasi Penggunaan Arkas 3.3 pada Pelaporan Penggunaan Dana Bos Sekolah Dasar Negeri 18 Bungo Pasang di Kota Padang - Windi Wulandari (Policy, Law and Political Research Center, 2022)
This study aims to look at the implementation of the use of Arkas 3.3 on the use of reporting funds for elementary school bosses at 18 Bungo Pasang in the Koto Tangah District in Padang City. This research is a quasi-qualitative method using the Simple Research Design (SRD) model. Selection of informants using purposive sampling technique. which is a data sampling technique with certain considerations. Thus the data collection is done by observation, interviews and documentation. Data analysis technique is done by data reduction, data presentation, verification and conclusion. The results showed that the user implementation of Arkas 3.3 was not in accordance with what was expected. But it didn't just stop there, of course, with obstacles that hindered the implementation of Arkas in the report, the implementation team tried to find a good solution. However, in some indicators the implementation has not been fulfilled in its entirety due to the lack of trained implementers in using the Rkas Application (ARKAS) during reporting. As well as in the activity there are obstacles that hinder the implementation of the use of Arkas to run optimally. Among them are the limited number of personnel in the implementation team for the use of Arkas in schools and the limited emergency funds at 18 Bungo Pasang Elementary School in Koto Tangah District.